Erratum - Editorial Office, Turkish Journal of Gastroenterology (Turkish Journal of Gastroenterology, 2015)
Abstract In the article by Yakar et al., entitled “The relationship of recurrent aphthous stomatitis and Helicobacter pylori, cytokine gene polymorphism and cobalamin” (Turk J Gastroenterol 2015; 26: 304-308) that was published in the July 2015 issue of Turkish Journal of Gastroenterology, one of the contributing authors was erroneously omitted from the author list. Upon receipt of the written request of the contributing authors, the Editorial Board reviewed the case and approved the author list to be corrected as follows. The corrected author list is provided below; Tolga Yakar, Ender, Serin, Arif Mansur Coşar, Didem Arslan Taş, Fatma Belgin Ataç Author contributions: Concept - E.S.; Design - T.Y., E.S.; Supervision - E.S.; Resource - A.M.C., T.Y., E.S.; Materials - T.Y., A.M.C.; Data Collection &/or Processing - T.Y., A.M.C., D.A.T., F.B.A.; Analysis &/or Interpretation - T.Y., E.S.; Literature Search - T.Y.; Writing - T.Y.; Critical Reviews - E.S.